2022
DOI: 10.1007/s41999-022-00702-9
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing practices, habits and attitudes of geriatricians and geriatricians-in-training across Europe: a large web-based survey

Abstract: Purpose To provide an overview of the current deprescribing attitudes, practices, and approaches of geriatricians and geriatricians-in-training across Europe. Methods An online survey was disseminated among European geriatricians and geriatricians-in-training. The survey comprised Likert scale and multiple-choice questions on deprescribing approaches and practices, deprescribing education and knowledge, and facilitators/barriers of deprescribing. Responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In fact, Essa et al recently demonstrated that a multispecialty multidisciplinary intervention reduced hospitalizations due to adverse drug reactions by significantly reducing the anticholinergic burden in patients with HF[ 41 ]. In particular, a multidisciplinary team could be crucial for the following actions: optimize HF therapy by prescribing appropriate HF-related drugs in line with guideline recommendations, such as ARNI, BB, SGLT2i, and MRA (“good” polypharmacy); deprescribing or reconsidering the dose of HF-related drugs that may increase the risk of negative effects such as orthostatic hypotension and fall in older adults with frailty, assuming administration of diuretics and/or SGLT2i; deprescription of HF-unrelated drugs such as benzodiazepines, antihistamines, anticholinergics and antipsychotics that may increase risk of falls, cognitive dysfunction, and functional decline[ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Essa et al recently demonstrated that a multispecialty multidisciplinary intervention reduced hospitalizations due to adverse drug reactions by significantly reducing the anticholinergic burden in patients with HF[ 41 ]. In particular, a multidisciplinary team could be crucial for the following actions: optimize HF therapy by prescribing appropriate HF-related drugs in line with guideline recommendations, such as ARNI, BB, SGLT2i, and MRA (“good” polypharmacy); deprescribing or reconsidering the dose of HF-related drugs that may increase the risk of negative effects such as orthostatic hypotension and fall in older adults with frailty, assuming administration of diuretics and/or SGLT2i; deprescription of HF-unrelated drugs such as benzodiazepines, antihistamines, anticholinergics and antipsychotics that may increase risk of falls, cognitive dysfunction, and functional decline[ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors contribute to prescribing inertia in primary care in Greece and other European countries: lack of time, lack of information sharing among primary care practitioners and specialists, lack of structured special geriatric education [ 28 , 29 ], inadequate numbers of health workforce and inadequate financial motivation [ 30 ]. It should also be noted that part of our data was based on self-report of the participants, so it is possible that patients may have failed to mention certain medical conditions, leading to a false identification of STOPP PIMs.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent European survey among geriatricians and geriatricians-in-training, the most important barriers for deprescribing were patients’ unwillingness, fear of negative consequences, lack of time, and poor communication between multiple prescribers [ 57 ]. The respondents stated that their future deprescribing activities would probably increase with improved information sharing between various prescribers, deprescribing recommendations in guidelines, and increased education and training [ 57 ].…”
Section: How To Perform a Fall-risk-increasing Drugs Medication Reviewmentioning
confidence: 99%